2003
DOI: 10.1002/hyp.1221
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for hillslope hydrologists: spatially distributed groundwater level and soilwater content measured using electromagnetic induction

Abstract: Abstract:New methods for obtaining and quantifying spatially distributed subsurface moisture are a high research priority in process hydrology. We use simple linear regression analyses to compare terrain electrical conductivity measurements (EC) derived from multiple electromagnetic induction (EMI) frequencies to a distributed grid of water-table depth and soil-moisture measurements in a highly instrumented 50 by 50 m hillslope in Putnam County, New York. Two null hypotheses were tested: H0 1 , there is no rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 14 publications
2
51
0
Order By: Relevance
“…We assumed that the change in soil water content was the main control of the temporal variation in ECa values during our repeated EMI surveys from January to June 2008 (note that all temperatures were corrected to a standard value). This is consistent with some previous studies that reported strong correlation between soil ECa and soil water storage (e.g., Sherlock and McDonnell, 2003;Reedy and Scalon, 2003). Thus, the higher and less stable ECa values in areas closer to the simulated flow paths (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We assumed that the change in soil water content was the main control of the temporal variation in ECa values during our repeated EMI surveys from January to June 2008 (note that all temperatures were corrected to a standard value). This is consistent with some previous studies that reported strong correlation between soil ECa and soil water storage (e.g., Sherlock and McDonnell, 2003;Reedy and Scalon, 2003). Thus, the higher and less stable ECa values in areas closer to the simulated flow paths (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have used soil ECa from EMI surveys to represent soil water content. For example, Sherlock and McDonnell (2003) reported that soil ECa from EM38 (Geonics, Mississauga, Canada) vertical dipole mode could explain over 70% of gravimetrically determined soil-water variance. Reedy and Scanlon (2003) used the same sensor to explain 80% of the averaged volumetric water content in the soil profile.…”
Section: Introductionmentioning
confidence: 99%
“…Less destructive methods such as ground penetrating radar, fibre optics, and electrical conductivity have been tested, but they require expensive equipment and have seen limited successes (e.g. Holden et al, 2002;Sherlock and McDonnell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Burns et al [2005], Sherlock and McDonnell [2003], and Heisig [2000], working in the New York City (NYC) water supply area, and Poor and McDonnell [2007] working in Oregon analyzed runoff production from catchments in a mix of land uses. While peak flows increase with development, there is also some evidence of base flow and nitrate export augmentation by septic fields in the New York catchments.…”
Section: Introductionmentioning
confidence: 99%